Conversion of hemicellulose from kenaf core fiber to xylose through dilute sulfuric acid hydrolysis - William Judiawan; Yanni Sudiyani; Elda Nurnasari (Jurnal Kimia Terapan Indonesia, 2019)
Kenaf (Hibiscus cannabinus) is a lignocellulosic plant that is usually utilized as a fiber source for sack production. The core from kenaf fiber has not been utilized yet in Indonesia, therefore it is still considered as a waste. Hemicellulose from kenaf core can be hydrolyzed to xylose through dilute sulfuric acid hydrolysis in high temperature. Hydrolysis in this study was done by using autoclave at 121â„ƒ and 10% (m/v) biomass: acid ratio for 15 and 45 minutes with a variation on acid concentration (2%, 4%, and 6% v/v). Xylose concentration in the hydrolyzate tends to increase with higher acid concentration and longer heating time. 6% (v/v) sulfuric acid concentration and 45 minutes of heating time produce the highest xylose concentration (20.53 gr/L) and yield (86.50%)